2022
DOI: 10.1093/lifemeta/loac032
|View full text |Cite
|
Sign up to set email alerts
|

Acetylation of PPARγ in macrophages promotes visceral fat degeneration in obesity

Abstract: Obesity is characterized by chronic, low-grade inflammation, which is driven by macrophage infiltration of adipose tissue. PPARγ is well established to have an anti-inflammatory function in macrophages, but the mechanism that regulates its function in these cells remains to be fully elucidated. PPARγ undergoes post-translational modifications (PTMs), including acetylation, to mediate ligand responses, including on metabolic functions. Here, we report that PPARγ acetylation in macrophages promotes their infiltr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 55 publications
0
3
0
Order By: Relevance
“…In this study, we confirmed metformin-induced increase in proinflammatory cytokines and suppression of SS FI in acute RC tendon rupture. Proinflammatory cytokines, released by immune cells under inflammatory conditions, play a pivotal role in muscle fat degeneration [ 14 , 28 , 29 ]. Metformin has the potential to activate T cells and macrophages and modulate adipocyte function [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we confirmed metformin-induced increase in proinflammatory cytokines and suppression of SS FI in acute RC tendon rupture. Proinflammatory cytokines, released by immune cells under inflammatory conditions, play a pivotal role in muscle fat degeneration [ 14 , 28 , 29 ]. Metformin has the potential to activate T cells and macrophages and modulate adipocyte function [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…The operation of GTTs and ITTs was performed as reported previously 46 48 . In brief, for GTTs, the mice were maintained an overnight (16 hours) fasting, and then the glucose (2 g/Kg body weight) was intraperitoneally injected into mice.…”
Section: Methodsmentioning
confidence: 99%
“…PPARγ plays an important role in regulation of cell metabolism and function. Constitutive acetylation of PPARγ in macrophages impedes their ability to skew toward anti-inflammatory state, and mice with constitutive acetylation-mimetic form of PPARγ in macrophages shows heightened macrophage infiltration to adipose tissue and activation toward pro-inflammatory state ( 146 ). In atherosclerosis, multiple macrophage populations detected in the plaque and vessel wall have at least some characteristics of MMe and can be accounted also as inflammatory macrophages.…”
Section: Myeloid Cells In Adipose Tissue and Atherosclerosismentioning
confidence: 99%